Study on the hygroscopicity of PET foam sandwich structure - Hao Liu; Jian He; Dongyuan Xie; Qichao Xue; Quansheng Peng (Advances in Mechanical Engineering, 2021)
Polyethylene terephthalate (PET) foam sandwich structure is widely used in the fields of construction, aerospace and shipbuilding. We have conducted research on its hygroscopic phenomenon. Take different sizes of GFRP panels, PET foam and PET foam sandwich structure for moisture absorption tests, analyze the data on the basis of the classic Fick’s law of diffusion to obtain the moisture absorption curves of each sample. And get the diffusion coefficient of the specimen. Then, we use the multi-physics software COMSOL to model and analyze the moisture absorption properties of the specified samples. The moisture absorption curve obtained by theoretical calculation was compared with the experimental moisture absorption curve, and the results showed that the two Good agreement. Tests have proved that the moisture absorption performance of PET foam is much greater than that of GFRP panel material, and the relative moisture absorption is related to the specific surface area of the sample. In the PET foam sandwich structure, the GFRP panel can effectively inhibit the hygroscopicity of the PET foam and has an excellent protective effect on the PET foam.